2023
DOI: 10.3390/microorganisms11030725
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Multidrug Resistance in Strains of Listeria monocytogenes Recovered from the Anaerobic Co-Digestion Sludge Contained in a Single Stage Steel Biodigester: Implications for Antimicrobial Stewardship

Abstract: L. monocytogenes is a zoonotic foodborne pathogen with inherent adaptability to tolerate environmental and physiological stresses, thereby causing severe disease outbreaks. Antibiotic resistant foodborne pathogens are a challenge to the food industry. A total of 18 samples were pooled from a bio-digester co-digesting swine manure/pinewood sawdust, and evaluated for the occurrence of bacterium plus total viable counts using the spread plate method. The recovered bacterial isolates were presumptively identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 89 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Although there is a natural resistance, acquired resistance has increasingly emerged in foodborne and human strains. This resistance reportedly stems from the routine use of antibiotics in farms or livestock ( Kayode and Okoh, 2023 ; Manyi-Loh et al, 2023 ). This acquired resistance requires a constant surveillance to provide adequate treatment for listeriosis and control its spread.…”
Section: Treatmentmentioning
confidence: 99%
“…Although there is a natural resistance, acquired resistance has increasingly emerged in foodborne and human strains. This resistance reportedly stems from the routine use of antibiotics in farms or livestock ( Kayode and Okoh, 2023 ; Manyi-Loh et al, 2023 ). This acquired resistance requires a constant surveillance to provide adequate treatment for listeriosis and control its spread.…”
Section: Treatmentmentioning
confidence: 99%
“…Lignocellulosic biomass is the group of most commonly generated waste in agricultural, agrifood, forestry and household production [22]. According to Paul and Dutta [57], the resulting byproducts can be classified as agricultural and forestry residues, as well as grass, energy crops and woody biomass.…”
Section: Structure and Composition Of Lignocellulosic Biomassmentioning
confidence: 99%
“…In addition, a major technical challenge is the storage of surplus light and wind energy. Many years of research have shown that an ideal alternative to the problem in question, which is irrespective of weather conditions, is the production of energy in the form of biogas from plant waste biomass [21][22][23]. Majeed et al [2] estimate that bioenergy generated from biomass is capable of meeting almost 40% of global energy demand.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations